AB0295 Clinical study on etanercept combined with tripterygium wilfordii polyglycoside for treatment of eldly rheumatoid arthritis. (23rd January 2014) - Ye, Z.; He, W.; Yin, Z.; Gao, J.; Xie, Y.
Abstract : Objectives: To evaluate the efficacy and safety of etanercept plus Tripterygium wilfordii polyglycoside(TWP) in elderly patients with active rheumatoid arthritis(RA). Methods: 46 elderly patients with active RA were randomized to the treatment group ( n = 24) and the control group ( n = 22). The former was treated with ETN ( injected with 50mg/week subcutaneously, after 3 months, 25mg/week) along with TWP(10mg, tid) ; the latter was treated with ETN and MTX (10mg/week). The whole course lasted 24 weeks, patients were assessed at weeks 0, 2, 6, 14 and 24. The change from baseline in pain, tender joint count, swollen joint count, health assessment (HAQ), patient's global assessment, physician's global assessment, ESR and CRP were evaluated. The curative effect was statistically evaluated by the United States Institute of Rheumatology ACR 20, ACR50 and ACR70 improvement criteria. Meanwhile adverse events were recorded and evaluated. Results: At week 2, the ACR20 was achieved in 58% of patients receiving ETN plus TWP, compared with 56% of patients receiving ETN plus MTX(p>0.05). The results for other clinical signs and symptoms and quality of life showed no difference between these two groups(P>0.05). At week 24, the ACR20 improvement was achieved in 80.2% of patients receiving ETN plus TWP, compared with 78% of patients receiving ETN plus MTX(p>0.05). There was no significant difference between the two groups in adverse effects. Conclusions: These two regimens of ETN plus TWP and ETN plus MTX all can improve the clinical signs and symptoms and quality of life, There was no difference between these two groups in efficacy, and they were well tolerated in the treatment of elderly patients with active RA. Disclosure of Interest: None Declared